Swimming for children and adolescents with asthma - Geiger, Katharina; Henschke, Nicholas (British journal of sports medicine, 2015)
This section features a recent systematic review that is indexed on PEDro, the Physiotherapy Evidence Database (http://www.pedro.org.au). PEDro is a free, web-based database of evidence relevant to physiotherapy. - - ▸ Beggs S, Foong YC, Le HCT, Noor D, Wood-Baker R, Walters JAE. Swimming training for asthma in children and adolescents aged 18 years and under. Cochrane Database Syst Reviews 2013;(4):CD009607. - - Swimming is often recommended as a form of physical activity for children with asthma. It is proposed to be superior to other forms of exercise for children with asthma due to the humidified and warm air, low pollen count exposure and hydrostatic pressure on the thoracic wall.1 However, some studies have raised concerns in relation to the potential proasthmatic effect of chlorinated pools.2 ,3 - - The aim of the systematic review was to determine the effectiveness and safety of swimming training as an intervention for asthma in children and adolescents. - - An electronic search was performed using the Cochrane Airways Group Specialised Register of trials, as well as the CENTRAL, PubMed, CINAHL and EMBASE databases in July …
First published February 18, 2014
Gesehen am 17.06.2020
Keywords: Rezension